Sustainability in Architecture of traditional Sasak settlements in Lombok - Agus Zulkarnain Arief; Achmad Tutut Subadyo (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Sasak is one of the Indonesian indigenous tribes who live in the island of Lombok. Until now, they still maintain the customs and culture as well as settling in Sembalun, Senaru, Segenter, and Sade. The Large of Sasak traditional settlement area in Lombok is not increased so that it feared the carrying capacity will be exceeded and could lead to a shift of customs and culture. This paper (1) to formulate the concept of a traditional Sasak sustainability settlement, (2) reconstruct the conception and typology of layout, mass configuration, space-organization, structure and building construction homes custom of Sasak, to analyze the sustainability level of Sasak traditional settlement used questionnaires Community Sustainability Analysis. The results obtained in this study is the traditional settlement of the Sasak people - PTSDS is in conformity with the ecovillage concept of Global Ecovillage Network. It is evident from the analysis of data by CSA which finds the total in 1226; with the value of the ecological aspect, the social aspect and the spiritual aspect, respectively 432, 373 and 421, which means the Sasak people - PTSDS shows very good progress on sustainability.